Crude Palm Oil (CPO) Quality Analyze of Elais guineensis at Palm Oil Mill PT. Sinar Pandawa, Labuhanbatu Regency (Based on Free Fatty Acid Levels, Water Content, and Impurities) - Shidiq, Muhammad; Lestari, Widya; Saragih, Siti Hartati Yusida (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The primary need for cooking oil or edible oil, the demand for cooking oil raw materials increases from year to year, this increase forces producers of crude palm oil (CPO) to compete to produce quality CPO products. PT. Sinar Pandawa, which is located in the Sennah plantation village, Batang downstream district, Labuhan Batu district, is one of the companies that produce CPO. Therefore, this study aims to determine the quality of CPO PT. Sinar Pandawa has good quality by using an analysis process of free fatty acid levels, namely the amount of free fatty acids resulting from hydrolysis and fat oxidation reactions, water content, namely the amount of water content in CPO and levels of impurities are foreign substances that do not dissolve. The method used in this research is titration using 0.1 NaOH solution for analysis of free fatty acid levels. The oven is open for moisture analysis i.e. heating the sample until the remaining water evaporates. Gravimetry for analysis of impurities content by filtering the sample using Whatman filter paper. The results show that the quality of CPO at PT. Sinar Pandawa which has the highest levels of fatty acids at 5.08%, water content of 0.35% and dirt content of 0.034%. The results of the analysis that has been carried out stated that the quality of CPO PT. Sinar Pandawa has not met the quality standards of SNI. The high value of each parameter, namely free fatty acid content, water content and dirt content with test values in accordance with SNI-2901-2006 maximum free fatty acid content of 5%, 0.25% water content and 0.25% dirt content indicates a lack of quality. CPO produced by PT. Sinar Pandawa due to lack of quality control